2008
DOI: 10.1016/j.jhealeco.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Aversion to health inequalities and priority setting in health care

Abstract: Traditionally aversion to health inequality is modelled through a concave utility function over health outcomes. Bleichrodt et al. (2004) have suggested a "dual" approach based on the introduction of explicit equity weights. The purpose of this paper is to analyze how priorities in health care are determined in the framework of these two models. It turns out that policy implications are highly sensitive to the choice of the model that will represent aversion to health inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…In a recent paper,Bleichrodt et al (2008) compared some priority setting's results under both models and showed that policy implications could be highly sensitive to the choice of model.…”
mentioning
confidence: 99%
“…In a recent paper,Bleichrodt et al (2008) compared some priority setting's results under both models and showed that policy implications could be highly sensitive to the choice of model.…”
mentioning
confidence: 99%
“…Then for all health improvements ( w, x ) and ( y, z ) in H × H , for all positive integers m and n , and for all policies c 1 = 〈( w 1 , x 1 ), ... , ( w m , x m ), 0 m+1 , ... , 0 m+n 〉 and c 2 = 〈0 1 , ... , 0 m , ( y m+1 , z m+1 ), ... , ( y m+n , z m+n )〉 in C for which c 1 ≥ c 2 , the statements (i) and (ii) are equivalent:

The preference relation, ≥, satisfies Marginality (Definition 1) and Anonymity (Definition 2).

There exists a positive real function U on H × H such that c 1 ≥ c 2 if and only if nmU(w,x)U(y,z).

With Theorem 4.1 the utility function over health state improvements takes an additive form (Fishburn, 1965; Keeney & Raiffa, 1993). The additive form can accommodate some concerns about inequality (Atkinson, 1970), but not all (Bleichrodt, Crainich & Eeckhoudt, 2008). We next characterize a person tradeoff for which preference for health state improvements is represented by health state value differences, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we will say that social preferences display inequality aversion if a homogeneous population with a certainty‐equivalent health level 1zHiitalicCE is preferred to a heterogeneous population in which individual i has a certainty‐equivalent health level HiitalicCE, that is, if U1ZHiitalicCE1ZUHiCE. Clearly, this is true if U ′ ′ ( x ) < 0. We will therefore refer to Inormala=U(x)U(x) as the index of absolute inequality aversion and to Inormalr=U(x)U(x)x as the index of relative inequality aversion. Remark When only ex‐post outcomes are analyzed (i.e., health levels after the state of nature is revealed), it is natural to define inequality aversion with respect to differences in individual health levels (Wagstaff, ; Dolan, ; Bleichrodt et al ., ). So, for example, concavity of the utility function implies that it is preferable to increase the health level of an individual with poor health rather than the health level of an individual in good health .…”
Section: Social Preferencesmentioning
confidence: 97%